"Corporate governance and its relationship to the quality of financial statements in Libyan economic institutions "An analytical study from the point of view of academics and professionals in the southern region - Ahmed, Ibrahim Al-Mahdi; Al-Saleh, Khaled Al-Kilani; Hamidi, Youssef Mamdou (Journal of Pure & Applied Sciences, 2021)
This study aimed to identify the importance of applying the principles of good corporate governance. It will lead to achieve the desired purpose; which is the quality of financial statements and improvement in financial performance. In order to achieve the objectives of the study, the descriptive analytical approach was used. Questionnaire was the mainly used method to collect the data for the purpose of the study. The participants of this study were academics, accountants and reviewers. After analyzing the data and testing hypotheses, the findings of this study showed great results. The group showed achievement on the application of the principles of corporate governance which contributed in an acceptable manner in order to achieve the quality of financial statements.  It has achieved as a result of its application which improved in the majority of financial performance indicators and to varying degrees.